Revisiting the picturesque: The preschool building as garden - Nordmark, Isabell (My University, 2022)
Research suggest that the natural environment supports children’s development, both by providing a wealth of objects to aid in knowledge formation, and also in providing a stimulating, dynamic setting that engages children emotionally. In recent years nature preschools, where children spend more time outdoors, are increasingly common. However, the preschool buildings that house the indoor activities of nature preschools largely correspond to those of conventional preschools. Framing this project is the thought; might it be possible to create a built environment that has the qualities, and benefits, of the natural environment? A natural appearence was important in the 18th-century picturesque landscape garden. The style was marked by asymmetry, irregular shapes, partially concealed views, oblique movement, and individual “scenes” with varying characters. The specific approaches to making space in the landscape garden were meant to stimulate movement, curiosity, and imagination. This thesis explores how some of the qualities of nature may be reproduced in architecture by engaging the 18th-century landscape garden as a limited milieu of the larger natural environment. The project begins with a literature study of 18th-century writing on landscape gardening. The study focuses on how the properties of view, movement, character and variety were used in the landscape garden, to create picturesque space. The second part of the project is concerned with finding and developing tools for configuring space, to create architecture that retains the qualities of picturesque space. At last, the tools are tested in a design project—applied to the program of a preschool, on a site in Gothenburg—with the aim of transferring the qualities of space in the picturesque landscape garden to the built environment. Ideally, this would serve as a supportive backdrop to children's development; through sparking movement, curiosity, and imagination.
Keywords: Landscape gardening; Picturesque; Preschool; Movement; Imagination; Nature; History